Docência universitária: o professor de Educação Física no curso de Educação Física - Lacerda, Patrícia Belchior de Oliveira (2007)
This research aims to the theme of the academical teaching, treated nowadays by researchers all over the world. Particularly in Physical Education, it is observed a certain lack of scientific studies which deal with the academical educational practice focusing on the association of the curricular contents with epistemological principles, political-social, cultural and which discuss the quality of the interpersonal relationships between teachers and students. From the diversity of ways of thinking and analyzing the academical teaching, especially the performance of the teacher of Physical Education in IES, arouses as a research problem how do the academical teachers, linked to the Physical Education Major from a public university from Minas Gerais, interpret their own education and professional practice, from the awareness of their academic experiences, that emphasizes the interpersonal relationships, in the planning and in the teaching and learning processes that they implement. Starting from this problem, it is aimed to consider the possible ways of how these teachers interpret their own education and professional practice, in order to understand the relationships that they establish amongst themselves and with the students, while educators, as well as their role in the education on the humanization process. The theoretical referential of this work discusses the Academical Teaching, in a general way, mentioning Tardif and Lessard (2005), Pimenta (2005) and Masetto (1998). It is also mentioned the Academical Teaching in Physical Education, with the contribution of Taffarel and Santos Júnior (2005), Beltrão (2002) and Oro (1994), among others. The first chapter, "Academical Teaching", discusses the general aspects of the academical teaching. The second chapter, Academical Teaching in Physical Education", discusses the comprehension of the teacher's practice in Physical Education in the researched IES, through the categories: interpersonal relationships (RI), planning (P) and the process of teachinglearning (PEA). The third chapter, "Methodological Ways", discusses the methodology of the research, that involves the form and the conception of how the data were collected, analyzed and interpreted. The last chapter, The Physical Education Teacher's View", intends to present the data of the field survey, tabulated, analyzed and interpreted, as well as the results of the discussion, starting from the association and confrontation of these with the theoretical referential of the study. The research of quanti-qualitative approach develops from the answers of the thirteen university permanent teachers of a Physical Education major, to the questionnaire of 36 multiple choice questions, answered according to the Scale of Likert, Rego and Reis (2002), with space for comments and an open question at the end. In the interpretation of the subjects of the research, the results suggest, among others, that the education/qualification of the academical teacher of Physical Education is determined by the educational practice. The results also show that the teachers always create an atmosphere of mutual respect and acceptance of the students' ideas, although they do not always ask stimulating questions encouraging them to reasoning.